EVALUASI KEBIJAKAN PEMBINAAN APARAT DALAM PENINGKATAN KINERJA PELAYANAN PUBLIK DI KAMPUNG YOBEH DISTRIK SENTANI KABUPATEN JAYAPURA - Melda Sokoy; Yosephina Ohoiwutun; Nur Aedah (Universitas Cenderawasih, 2020)
The purpose of this study was to determine the performance of public services carried out by officials in the Yobeh Village, Sentani District, Jayapura Regency, and to find out the effect of the training carried out on the officers in the Yobeh village, Sentani district, Jayapua Regency. The research method used is descriptive qualitative to describe and analyze the evaluation of the implementation of the apparatus development policy of Yobeh village, Senani District, Jayapura Regency. The technique of determining the informants used was Pusposive, while the data collection included in-depth interviews. Data analysis in the form of data reduction, data display and conclusion. The results showed that first, the managerial approach and policy were the most dominant factors in the implementation of government apparatus development policies. Second, the village head is implementing the village apparatus development policy. Support in the form of policy facilities and infrastructure is tailored to the concept of the need for deliberations and meetings related to the implementation of the village program. The lack of guidance from other institutions such as the district and local governments has resulted in a lack of capacity of village officials in carrying out their duties and functions. Third, cultural factors are the most dominant factor in delivering quality public services.